Analisis Efektivitas Forklift 5 Ton Di PT XYZ Dengan Metode Overall Equipment Effectiveness - Lindra Rahmad Rizqi Julian; Faisal Manta; Kholiq Deliasgarin Radyantho; Hadhimas Dwi Haryono; I Made Ivan Cakra Sujana (AUSTENIT, 2025)
Forklifts play a vital role in ensuring the smooth production and distribution of materials in industrial environments. The effectiveness of forklift operation significantly influences productivity, particularly in the oil and gas sector, which demands high punctuality and efficiency. This study aims to analyze the operational effectiveness of a 5-ton forklift at PT XYZ by applying the Overall Equipment Effectiveness (OEE) method, which consists of three main components: availability, performance, and quality. In addition, the six big losses approach is used to identify the primary sources of inefficiency. The results show that the highest OEE value was recorded in June at 91.04% (availability 94.24%, performance 96.60%, and quality 100%), while the lowest was in July at 82.20%, falling below the world-class OEE benchmark of 85%. Fishbone diagram analysis indicates that idle and minor losses are the largest contributors, accounting for 61.9% of the total losses. These are mainly caused by human factors, such as low work discipline, insufficient operator skills in executing standard procedures, irregular work methods, and the absence of a real-time system for recording and reporting minor disturbances. Other supporting factors include limited direct supervision, excessive workload, and non-optimal preventive maintenance schedules. To address these issues, the study recommends improvements such as regular operator training, clearer and more structured work procedures, implementation of daily log sheets to record idle time, improvement of forklift operation routes to minimize obstacles, and routine preventive maintenance scheduling for critical components, including brakes, batteries, forks, and electrical systems.